Historical Roots of Impunity and Its Role in Perpetuating Corruption in Nepal - Ghimire, Dipesh K. (Molung Educational Frontier, 2025)
Corruption, a pervasive global issue, is particularly pronounced in countries where impunity and lawlessness prevail. This article examines the complex relationship between impunity and corruption, highlighting how unchecked power and weak legal frameworks allow corruption to flourish. In Nepal, the historical context of impunity, dating back to the Rana regime and continuing through various political systems, has significantly contributed to the institutionalization of corruption. The lack of accountability for the Rana family and high-level officials has created an environment where corruption thrives unchallenged during Rana Regime. Instances from Nepal's history, such as the Panchayat's "Panchakhat Mafi" and the vacuum in the Commission for the Investigation of Abuse of Authority (CIAA) in long time in republican regime, illustrate how legal provisions have been manipulated to protect the powerful. This study combined historical analysis and semi-structured interviews with key informants to examine the evolution of impunity and its impact on corruption in Nepal, using thematic analysis to identify patterns and assess reforms. This study underscores that efforts to combat corruption will remain ineffective without robust watchdog institutions and genuine enforcement of the law. The article argues that dismantling impunity is essential for eradicating corruption and achieving good governance in Nepal.